Influence of environmental factors in the atmospheric corrosion of copper in the presence of propionic acid (2009)
Exposure time, pollutant concentration, and relative humidity (RH) are important environmental variables for the atmospheric corrosion of copper in the presence of propionic acid vapors. This paper shows the most outstanding results into the effect of these variables. This study was carried out by mean of exposures at dynamic conditions in 260, 380, and 680 ppbv propionic acid, with relative humidities of 70% and 90%. The effect of the propionic acid was also evaluated in static conditions with 4, 40, and 120 ppmv propionic acid with relative humidities of 40%, 80%, and 100% RH. All the samples were evaluated by triplicate within 21 days of exposure. The corrosion rate was used to quantify the degradation of copper by mean of weight loss and coulometric reduction technique. Coulometric reduction indicates that the charge needed to reduce the oxides increases as exposure time, relative humidity and pollutant concentration increases. On the other hand, the corrosion rate determined gravimetrically, confirms that at a higher relative humidity and higher propionic acid concentration the copper deterioration is also higher